Synthesis and characterization of polyesters from 2,3-bis (4 `-hydroxy phenyl) quinoxaline and 2,3-bis (2 `-hydroxynaphthalene-6 `-yl) quinoxaline - Patil, V. B.; Medhi, M.; Bhairamadgi, Nagendra S.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
Two bisphenols containing pendant, quinoxaline moiety; 2,3-bis (4'-hydroxy phenyl) quinoxaline (BHPQ) and 2,3-bis (2'-hydroxynaphthalene-6-yl) quinoxaline (BHNQ) were synthesized and characterized by FT-IR, (1)H, (13)C NMR and mass spectrometry. Aromatic polyesters and copolyesters were prepared by interfacial polymerization from BHPQ or BHNQ and isophthaloyl chloride or terephthaloyl chloride or a mixture of different mole proportions of (IPC + TPC). These polyesters and copolyesters were characterized by spectroscopic technique, viscosity measurement, solubility, thermal stability. DSC and XRD. Polymers had moderate to high molecular weights as evidenced by the inherent viscosities in the range 0.35-0.78 dL/g for BHPQ series and 0.27-0.52 dL/g for BHNQ series. BHPQ polyesters and copolyesters dissolved in m-cresol, NMP and conc. H(2)SO(4) whereas, BHNQ polyesters and copolyesters were readily soluble in NMP, DMAc, (TCE + phenol) and partly soluble in solvent like CHCl(3), pyridine, etc. Wide angle X-ray diffraction (WAXD) results showed that introduction of quinoxaline moiety into polymer chain and aromatic phenyl/rigid naphthyl structures lead to crystalinity. Differentional scanning calorimetry of BHNQ polyesters showed the glass transition temperatures in the range of 131-151 degrees C. BHPQ polyesters did not show any weight loss below 330 degrees C and retained 27-55% weight at 900 degrees C when investigated by TGA under nitrogen atmosphere demonstrating good thermal stability BHNQderived polyesters showed initial decomposition temperatures in range 211-234 degrees C. The structure-property relationships for the mentioned polyesters are analyzed, as these polyesters are of interest as materials for electronics, microelectronics and membrane separation. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 2; 3-Bis (2 `-hydroxynaphthalene-6 `-yl) quinoxaline; 3-Bis (4 `-hydroxy phenyl) quinoxaline; Aromatic polyesters; Glass transition temperature; solubility; Thermal properties